Leucopaxillus giganteus mycelium: effect of nitrogen source on organic acids and alkaloids - Pereira, David M. (2008)
ln order to study the influence 01 lour inorganic nitrogen sources (NH4N03, NaN02, KN03 and (NH4)2HP04) on the chemical composition 01 Leucopaxillus giganteus mushroom mycelium, its organic acids profile was determined by HPLC-UV and total alkaloids content was assessed by a spectrophotometric method, alter precipitation by Dragendorlf's reagent. lhe results showed that L. giganteus presented an organic acids profile composed by oxalicis-aconitic, citric and lumaric acids, being citric acid the major one.